Patient's perception towards cosmetic dentistry in relation to Islamic principle - Faizah Abdul Fatah; Norlela Yacob; Haslinda Ramli; Norazlina Mohammad; Diana Md Zahid; Mohd Nasir Abd Majid; Salleh, Ahmad Zaki (American Scientific Publishers, 2024)
Indexed by Scopus